Brucella Canis discospondylitis in a dog imported into the United Kingdom from Romania. Issue 4 (13th August 2021) - Escauriaza, Leticia; Reeve, Lizzie; Hahn, Harriet; Granger, Nicolas; Vandenberghe, Helene
Abstract: A 1‐year‐old female neutered Border collie‐cross dog presented for investigation of pain of unknown origin, lethargy and pyrexia. The dog had entered the United Kingdom one and half months before and had been imported from Romania. Neurological examination suggested multifocal spinal pain. Magnetic resonance imaging of the vertebral column documented multiple sites of discospondylitis involving the vertebral column. Cerebrospinal fluid cytology was normal and Brucella canis antibody titres were markedly high (3+/200), which was consistent with a diagnosis of brucellosis. Treatment with amoxicillin/clavulanic acid and paracetamol was started which led to a clinical improvement. However, given the poor prognosis, risk of zoonosis, and following recommendation from Public Health England, the dog was euthanised. Brucella canis cases are increasingly reported in the United Kingdom. This case report raises the importance of considering Brucella as a differential diagnosis in dogs with multifocal spinal pain and pyrexia, particularly when imported from regions at risk such as the Eastern European countries.